The use of innovative technologies in the process of higher education ce matimatike - Рашевська, Наталя Василівна (Pedagogy of Higher and Secondary Education, 2013)
Rashevs’ka N. V. The use of innovative technologies in the process of higher education ce matimatike. In the article some form of organization learning higher mathematics on the model of blended learning using mobile information and communication technologies. Defined principles of higher mathematics learning of mobile ICT.